Anticancer Activity of Trisubstituted Pyrazoline Derivatives: Synthesis, Characterisation, and Computational Studies - Mazal, Sabah Motrud; Al Shuhaib, Zainab; Alharis, Raed Awad; Hussein, Kawkab Ali; Ismail, Sadiq Muhammad Hassan (Science and Technology Indonesia, 2026)
The search for new anticancer drugs that target apoptotic and autoimmune pathways is essential, as these pathways are crucial for maintaining cellular homeostasis and destroying cancer cells. In this study, eight trisubstituted pyrazoline derivatives (2a-d and 3e-h) were synthesised through a cyclocondensation reaction of chalcones with hydrazide derivatives (hydrazine hydrate and phenyl hydrazide). These derivatives were characterised using EI-MS, ¹H NMR, ¹³C NMR (both 1D and 2D), and ¹⁹F NMR spectra. Their cytotoxic activity against the MCF-7 tumour cell line was tested with the MTT assay. The results showed that compounds 2a-d had the most potent inhibitory effect on MCF-7 cell growth, with IC50 values of 19.46, 29.45, 44.15, and 26.37 µg/mL after 24 hours of exposure. Among them, compound 2a was the most potent. In comparison, compounds 3e-h had significantly higher IC50 values of 101.67, 75.99, 102.83, and 99.54 µg/mL, respectively, than the reference drug doxorubicin, which has an IC50 of 1.24 µg/mL. Additionally, docking of compound 2a showed good binding affinity values with the protein (PDB ID: 5T92) amino acid residues in different interactions: H-donor, H-acceptor, and H-pi, as well as two H-acceptor and pi-H interactions with the water and other amino acids. The most favourable binding pose corresponded to the lowest ΔG and exhibited robust pose quality. The molecular structures of compounds 2a-d were optimised using the B3LYP functional and the 6-311+G(d) basis set, and their quantum chemical properties were analysed through molecular orbital studies.